Pan-ROCK and ROCK2 Inhibitors Affect Dexamethasone-Treated 2D- and 3D-Cultured Human Trabecular Meshwork (HTM) Cells in Opposite Manners - Megumi Watanabe (MDPI AG, 2021)
Effects of a pan-ROCK-inhibitor, ripasudil (Rip), and a ROCK2 inhibitor, KD025 on dexamethasone (DEX)-treated human trabecular meshwork (HTM) cells as a model of steroid-induced glaucoma were investigated. In the presence of Rip or KD025, DEX-treated HTM cells were subjected to permeability analysis of 2D monolayer by transendothelial electrical resistance (TEER) and FITC–dextran permeability, physical properties, size and stiffness analysis (3D), and qPCR of extracellular matrix (ECM), and their modulators. DEX resulted in a significant increase in the permeability, as well as a large and stiff 3D spheroid, and those effects were inhibited by Rip. In contrast, KD025 exerted opposite effects on the physical properties (down-sizing and softening). Furthermore, DEX induced several changes of gene expressions of ECM and their modulators were also modulated differently by Rip and KD025. The present findings indicate that Rip and KD025 induced opposite effects toward 2D and 3D cell cultures of DEX-treated HTM cells.